EFEKTIVITAS METODE INKUIRI DALAM PEMBELAJARAN BIOLOGI MATERI SISTEM PENCERNAAN MANUSIA KELAS XI SMA NEGERI 4 PADANGSIDIMPUAN - DHARMA GYTA SARI HARAHAP (Jurnal Education and Development, 2019)
This research aims to see the existence that influence method of incuiri to result learn system direct material biology disgestion of class student human being of XI SMA Negeri 4 Padangsidimpuan. The population in this research is all class that consist of 3 class with amount of counted 108 students. Obtained data is hereinafter analized with two phase. First phase of descriptive analized to see picture in general from both variable. While phase both of statistical analysis to test the truth of hypothesis, do the hypothesis can be accepted or refused by at level of sycnyficant 5%, hence by statistical analysis by using correlation formula " r" product moment. Pursuant to calculation conducted to test specified hypothesis hence t count got equal to 1,23 and ttabel 0,62 at tbiged rust storey; level 95% or mistake storey, level 5% degree of freedom which ( dk) = N-2 = 54-2 = 25 obtained by t table = 0,62 so that if count = 1,23 bigger compare ttable = 0,62 ( 1,23 > 0,62). Its meaning, there are influence which is significant between cooperatif tife of method of incuiri to result of biological studing of system direct material disgestion of class student human of XI SMA Negeri 4 Padangsidimpuan.